General Doctor's Consultation Work Begins before Entering the Patient and does not End when Patient Comes Out - Jose Luis Turabian (International Journal of General Practice, 2020)
The consultation is the activity of meeting and communication between an individual and the doctor for the knowledge and solution of a health problem. In today's busy world of general medicine, constant demands for the general practitioner (GP) arise: she or he should not only make a diagnosis not only should make a differential diagnosis during consultation, but must also establish a good relationship, explore patient ideas, concerns and expectations and negotiate a management plan, taking into account limited resources, the quality framework and results, having Information technology skills, plus, the need to promote health during any consultation. Normally the GP has only 10 minutes to achieve all that, as well as to manage your own emotions, agendas and uncertainty. In this way, novice doctors may find it difficult to move in this situation of complexity, and they can also observe a gap in the literature that really guides them in practice. Rigorous preparation is the key to success for many endeavours. Some tips to perform an efficient and safe consultation work in general medicine are suggested: 1) Focus on the next patient; 2) Preparing the consultation before entering the patient, memorizing the patient's previous history; 3) Establishing a connection with the patient; 4) Remembering the elements that must be in each consultation (the current reason, update other previous processes, chronic diseases and continued attention,
Keywords: Consultation